Single and Combined Effects of Cypermethrin and UVR Pre-Exposure in the Microalgae Phaeodactylum Tricornutum - Cabrera, Joaquin (2021)
Coastal marine microalgae are exposed to anthropogenic pollutants, including pesticides from aquaculture/agriculture/household uses. Some microalgae species, such as Phaeodactylum tricornutum, can induce and accumulate UV-absorbing compounds (UACs) upon ultraviolet radiation (UVR) exposure to prevent deleterious effects. Tolerance mechanisms activated by natural stressors might also protect organisms from anthropogenic stressors. This work assesses the effects of the insecticide cypermethrin (Cyp) and UVR in the marine microalgae P tricornutum. Considering the pro-oxidant properties of both stressors and UACs’ induction in P tricornutum, lethal and sublethal effects of Cyp were tested in cultures with and without UVR acclimation. After a 24-h exposure to 10 μg L−1 of technical Cyp or culture medium, UACs, growth, glutathione-S-transferase activity (GST), sulfhydryl groups (SH-g), and lipid peroxidation (LPO) were analyzed. Results showed differences in terms of growth between Cyp and Cyp + UVR pre-exposure. UACs’ content was induced after UVR acclimation and diminished after 24 h of growth in control and UVR pre-treated cultures, while levels remained constant under Cyp exposure. A single Cyp exposure exerted GST induction, SH-g depletion, and LPO increments. In UVR-acclimatized treatments, oxidative stress responses showed similar or more pronounced effects than the single chemical exposure, suggesting a potential additive effect of the UVR acclimation. The contrasting effects of Cyp + UVR observed between growth and biochemical responses suggest different compensatory mechanisms that need to be further investigated. Also, it highlights the need to include both lethal and sublethal endpoints to understand microalgae’s tolerance and its significance in the multiple stressors’ context.